Pan-Cancer Analysis Reveals Disrupted Circadian Clock Associates With T Cell Exhaustion - Wu, Yingcheng; Tao, Baorui; Zhang, Tianyang; Fan, Yihui; Mao, Renfang (Frontiers in Immunology, 2019)
Although dysfunctional circadian clock has emerged as a hallmark of cancer, fundamental gaps remain in our understanding of the underlying mechanisms involved. Here, we systematically analyze the core genes of the circadian clock (CLOCK, ARNTL, ARNTL2, NPAS2, NR1D1, NR1D2, CRY1, CRY2, RORA, RORB, RORC, PER1, PER2, and PER3) across a broad range of cancers. To our surprise, core negative regulators (PER1, PER2, PER3, CRY1, and CRY2) are consistently downregulated, while core positive regulators show minimal alterations, indicating disrupted circadian clock in cancers. Such downregulation originates from copy number variations where heterozygous deletion predominates. The disrupted circadian clock is significantly associated with patient outcome. Further pathway enrichment analysis suggests that the circadian clock widely impacts 45 pathways such as the Ras signaling pathway and T cell receptor signaling pathway. By using state-of-the-art immune cell deconvolution and pathway quantification, we demonstrate that abnormal circadian clock contributes to T cell exhaustion and global upregulation of immune inhibitory molecules such as PD-L1 and CTLA-4. In summary, the rhythm of the circadian clock is disrupted in cancers. Abnormal circadian clock linked with immune evasion may serve as a potential hallmark of cancer.